For Consistent Code, Retell the Great Myths. (Communications of the ACM, 2012)
A letter to the editor is presented in response to the article "Coding Guidelines: Finding the Art in Science" by Robert Green and Henry Ledgard in the December 2011 issue concerning the need of consistency in computer programming habits.